Between solace and struggle: University students’ perceptions of music listening for managing depressive symptoms - Raymond Nyuke (UIN Maulana Malik Ibrahim Malang, 2026)
University students across the world are at high risk of depression with high prevalence rates in sub-Saharan Africa due to contextual stressors and limited access to mental health services. This causes students to employ self-directed coping strategies to manage depressive symptoms. One such strategy is music listening whose perceived effectiveness and challenges in this context are not well understood. This study examined the perspectives of twelve self-selected students at a university in Zimbabwe on the effectiveness and challenges of music listening for managing depressive symptoms. It adopted a qualitative descriptive phenomenological design. Data from semi-structured interviews were analysed using thematic analysis. Results revealed that students perceived music as an effective strategy for the elevation of mood, provision of solace and companionship, building a sense of agency and complementing other coping strategies. Perceived challenges included amplification of negative emotions, detachment from reality, frustration from mismatch between music and mood as well as overreliance which could deter seeking other forms of support. The results indicate the dual nature of music listening as a coping mechanism that both serve as a powerful self-regulation tool and a possible source of self-maladaptive rumination and avoidance. Such results demonstrate the necessity of combining knowledge about the current musical practices of the students with mental health promotion and advising students to use these practices more intentionally and in a balanced way.Keywords: depression; music listening; perceptions; university students; Zimbabwe